One-Pot Synthesis of 3,4-Dihydropyrimidin-2(1H)-ones Using Hydrochloric Acid- β-Cyclodextrin- Combined Catalysts - Zhou, Haixia; He, Miao; Liu, Chunsheng; Luo, Genxiang (Letters in Organic Chemistry, 2006)
An improved approach has been found to carry out the Biginelli reaction for the synthesis of 3,4- dihydropyrimidin- 2(1H)-one derivatives. This synthesis was performed in the presence of hydrochloric acid and β-cyclodextrin in ethanol solution. Compared with the classical Biginelli reaction conditions, this new approach has the advantage of excellent yields and short reaction time.
Keywords: One-pot